Are Innovation Networks in Need of a Conductor? Examining the Contribution of Network Managers in Low and High Complexity Settings. Issue 1 (February 2016) - Heidenreich, Sven; Landsperger, Johannes; Spieth, Patrick
Abstract : Innovation networks, like organizations, need to be managed thoroughly. With rising numbers and actor heterogeneity in an innovation network, the potential for organizations to create, distribute and acquire knowledge more efficiently increases, but the complexity of managing the network also increases. Having someone in place to gain insight into the participating organizations' structures, and to keep track of and coordinate the available and usable resources, represents a clear advantage. While scientific research and management practice have acknowledged the importance of network managers for network performance, little research effort is dedicated to empirically investigate and validate this theoretical proposition. This paper fills part of this gap by examining the influence of the simple existence of network managers on core management functions and performance outcomes in low and high complexity settings. Our results confirm that employing a network manager significantly improves core network management functions and relational as well as structural network performance, which in turn enhance goal achievement performance and network retention. Furthermore, our results from interaction analyses show that the network managers' contribution is even greater in high complexity settings.